A5.29 Spontaneous Production of Anti-Citrullinated Protein Antibodies in Cultures of Peripheral Blood Mononuclear Cells and Synovial Fluid Mononuclear Cells Isolated from Patients with Rheumatoid Arthritis. (25th February 2013) - Kerkman, Priscilla F; Rombouts, Yoann; Voort, Ellen IH van der; Trouw, Leendert A; Huizinga, Tom WJ; Toes, René EM; Scherer, Hans U
Abstract : Background and Objectives: Anti-citrullinated protein antibodies (ACPA) are among the most important molecular candidates that could drive the inflammatory immune response in a subset of patients with rheumatoid arthritis (RA). So far, however, little is known on the phenotype and functional characteristics of ACPA producing B cells. Therefore, we studied ACPA producing B cells using ex-vivo cultures of peripheral blood mononuclear cells (PBMC) and synovial fluid mononuclear cells (SFMC). Materials and Methods: PBMC as well as SFMC from patients with ACPA-positive RA were cultured in 96 well plates without the addition of exogenous stimuli. Cultures were maintained for several weeks, with weekly complete replacement of the culture medium. Every week, supernatants were assessed for the presence of ACPA-IgG and total IgG by ELISA. B cell subsets within the culture populations were determined by flow cytometry at several time points. Results: Circulating, spontaneously ACPA producing B cells were readily detectable in peripheral blood of ACPA positive RA patients, but not in ACPA negative RA patients or healthy donors. FACS sorting experiments comparing isolated B cell subsets located spontaneous ACPA production to the plasmablast compartment. Memory B cells were capable of ACPA production upon stimulation. In some culture wells, ACPA production was stable and detectable for up to 3 months. In a similar manner, we observed spontaneous, long-lasting ACPA production in (paired) SFMC cultures. The latter showed an up to 200 fold increase in ex vivo ACPA production compared to PBMC, but only a minor increase in the secretion of non-specific IgG. B cell numbers in PBMC and SFMC were comparable in the starting population. Conclusions: ACPA specific plasmablasts circulate in the peripheral blood of patients with ACPA positive RA. Upon isolation, peripheral blood B cells can secrete ACPA spontaneously for several months. This observation suggests that ACPA specific B cells are either continuously recruited from the memory compartment, or that a subset of ACPA specific plasmacells might have the capacity to survive for extended periods of time. In SFMC, the frequency of ACPA specific B cells is strongly increased. These observations point to a continuously active, ACPA specific immune response in RA.